Genome-wide analysis of the TCP gene family and their expression pattern in Cymbidium goeringii - Liu, Ding-Kun; Zhang, Cuili; Zhao, Xuewei; Ke, Shijie; Li, Yuanyuan; Zhang, Diyang; Zheng, Qinyao; Li, Ming-He; Lan, Siren; Liu, Zhong-Jian (Frontiers in Plant Science, 2022)
TCP proteins are plant-specific transcription factors considered to play an important role in plant growth and development. However, few related studies investigated the TCP gene trait and how it plays a role in growth and development of Orchidaceae. Here, we identified 14 TCP genes (CgTCPs) from the genome of the spring orchid Cymbidium goeringii. The phylogenetic analysis suggested that the genes were mainly divided into two classes as follows: four PCF genes (Class I), nine CIN genes and one CYC gene (Class II). The sequence analysis showed that the TCP proteins of C. goeringii contain four conserved regions (Basic, Helix, Loop, and Helix) in the TCP domain. The comparative analysis of the gene structure showed that the exon‒intron structure varied in the same clade, and some genes exhibited no introns. There are fewer CgTCP homologous gene pairs compared with Dendrobium catenatum and Phalaenopsis equestris, suggesting that the TCP genes in C. goeringii suffered more loss events. The cis-elements identified in the promoter region of CgTCPs were found to be mostly enriched in the function of light responsiveness, followed by MeJA and ABA responsiveness, indicating their roles in modulating light and phytohormones. The collinearity analysis revealed nearly one-to-one correspondence among TCPs in D. catenatum, P. equestris and C. goeringii. The expression profiles based on transcriptomic data and real-time reverse transcription-quantitative PCR (RT‒qPCR) revealed that the flower-specific expression of the TCP class II genes (CgCIN2, CgCIN5 and CgCIN6) may be related to the regulation of florescence. Altogether, this study provides a comprehensive analysis uncovering the underlying function of TCP genes in Orchidaceae.